Early functional proprioceptive stimulation in high spinal cord injury: a pilot study - Martinache, Florence; de Crouy, Anne-Claire; Boutin, Arnaud; Duranteau, Jacques; Vigué, Bernard (Frontiers in Rehabilitation Sciences, 2025)
IntroductionThe first months following a spinal cord injury (SCI) are crucial for promoting recovery. However, patients with high SCIs often require prolonged stays in intensive care units (ICUs), delaying optimal rehabilitation due to limited resources. This study examined the safety, feasibility, and effects on spasticity and muscle atrophy of an early rehabilitation technique using non-invasive sensory stimulation and called functional proprioceptive stimulation (FPS).Materials and methodsTen SCI patients were included in this randomized pilot study, with five receiving early FPS and five receiving sham stimulation. Both groups were treated using the Vibramoov, consisting of 12 computer-synchronized vibrators placed on the lower limbs. Treatment sessions lasted 30 min, four times a week, for up to 8 weeks. Spasticity was assessed using the Modified Ashworth Scale, Tardieu Scale, Spinal Cord Assessment Tool for Spastic Reflexes, and a patient self-evaluation with a visual analog scale. Muscle atrophy was evaluated through ultrasonography of rectus femoris thickness and cross-sectional area. The duration of the follow-up period ranged from 6 months to 1 year.ResultsTreatment began early, with a median of 4 days post-injury for both groups. The number of adverse events was similar between groups, with none linked to the intervention. No medium-term effects on spasticity or muscle atrophy could be identified. However, our results show a tendency toward a beneficial short-term effect of FPS on spasticity, observed for all spasticity measurements.DiscussionThis pilot study shows that early FPS is feasible and safe for SCI as early as the intensive care unit stage. We demonstrated that FPS induced a transient relaxation and spasticity reduction that could potentially enhance a rehabilitation session administered shortly after it, but larger studies are needed to determine the medium and long-term effects. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT05094752)